Drive for thinness as a women's strategy to avoid inferiority - Ferreira, C. (2013)
Ferreira, C., Pinto-Gouveia, J., & Duarte, C. (2013). Drive for thinness as a women's strategy to avoid inferiority. International Journal of Psychology and Psychological Therapy, 13(1), 15-29. http://www.ijpsy.com/volumen13/num1/344.html